A comparative study on heat transfer characterization of sodium alginate-based carbon nanotubes in a non-Newtonian fluid flow using a new local thermal nonequilibrium formulation. Issue 5 (14th July 2022) - Lalitha, K. R.; Veeranna, Y.; Ashok Reddy, D.; Sreenivasa, G.T.
Abstract: The current study elucidates the mass and heat transfer characteristics of Casson nanofluid flow over a stretching sheet in a porous medium (PM) subject to a lack of local thermal equilibrium (LTNE). The LTNE model is based on the energy balance of both solid and fluid phases. Hence, distinctive thermal profiles for both the fluid and solid phases are employed in this study. Further, owing to exceptional high intrinsic conductance performance, Carbon nanotubes (CNT's) show great potential to increase the thermal conductivity. In this connection, CNT's (single and multi-wall) are considered as suspended nanoparticles in the base fluid sodium alginate (SA). The equations of modeled physical problem are reduced by using a proper transformation, which are then numerically tackled by using the classical Runge-Kutta (RK) process with the shooting technique. The impact of the flow parameters on the thermal, concentration and velocity profiles along with skin friction, Nusselt and Sherwood numbers is explored and interpreted graphically. The results reveal that, SWCNT-sodium alginate Casson nanoliquid show improved heat transfer for growing values of porosity parameter. The fluid and solid phase thermal profiles of MWCNT-sodium alginate Casson nanoliquid is strongly stimulated by growing values of porosity-modified conductivity ratio parameter.